An investigation into the syntactic, semantic and cultural features of idioms denoting Life and death In english and vietnamese - Nguyễn Hoàng Trà My (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis is to study syntactic, semantic and cultural features of English and Vietnamese idioms denoting life and death. The analysis has investigated 240 idioms in English and Vietnamese together with numerous samples in dictionaries, short stories, prose and from Internet. The study aims at finding out similarities and differences of these idioms in term of syntactic, semantic and cultural features. Syntactically, analyzed idioms are under phrasal structures. In English and Vietnamese LDIs are under noun phrase, verb phrase, adjective phrase and prepositional phrase. Semantically, LDIs devided into life in general, rich and poor life, happy and unhappy life, simple and lavish life. Besides, the semantic fields about death include death in general, quality, age including young and old, and conditions comprising suddenness, difficulty, happiness and misfortune, glory and failure. In the aspect of cultural features, the similarities and differences in LDIs in two languages in consideration the cultural elements such as cultural symbols, religions, symbolic animals, symbolic plants, human body parts were found out. Besides the study also suggests some implications of finding for teaching and learning English as a foreign language in Vietnam as well as for further study is put forward.